Implementation of Al-Qur'an Learning with the Book Hubbul Ilmii Koran in Improving Al-Qur'an Reading at Griya Qur'an al-Inayah Pulung Ponorogo - Sutikno; Laksana , Sigit Dwi; Syamsul Arifin; Ichwanudin; Muhammad Azzamudin Syahapala (Institut Agama Islam Negeri Palangka Raya, 2024)
This study aims to analyze the application of the Hubbul Ilmii method in improving the ability to read the Qur'an in early childhood at Griya Qur'an al-Inayah Pulung Ponorogo. The research uses a qualitative approach with a descriptive method to describe in depth the process of planning, implementing, and evaluating Qur'an learning. Data were collected through participatory observation, in-depth interviews with caregivers and ustadzah, and documentation of learning activities, with subjects consisting of 50 active students and teaching staff. Data analysis was carried out using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawn, with triangulation as a data validity technique. The results of the study showed that the application of the Hubbul Ilmii method significantly improved the ability to read the Qur'an within 36 meetings. Before learning, 68% of students were in the category of